How good is teleworking? Development and validation of the tele attitude scale - Junça-Silva, A.; Caetano, A. (Quality and Quantity, 2024)
The objective of this study was to develop and validate a measure called the Tele Attitude Scale (TAS). This measure aims to evaluate relevant aspects of the teleworking experience related to its perceived effects regarding, for instance: job characteristics, perceived productivity, quality of work-related interactions, work-non-work balance, and well-being. Four studies were conducted between 2021 and 2022. First, a qualitative study was conducted to develop the scale (N=52). Afterward, a second study to explore the scale’s factorial structure (N=602) was developed. A third study served to analyze its internal validity and reliability (N=232). A fourth study analyzed the criterion validity of the scale by exploring its correlations with measures of health, affect, and performance (N= 837 teleworkers). The findings revealed that the 10-item scale accounted for a unique factor and that it was a reliable measure. Moreover, the results also showed that the scale was significantly related to measures of health, affect, and performance, thus supporting its convergent and criterion validity. This research advances the knowledge about telework by proposing a user-friendly scale to measure teleworking, specifically how workers perceive their experience of it and how it may impact them at several levels. Thus, the TAS can not only fill a gap in the research but also help organizations evaluate and support teleworkers’ needs and subsequent satisfaction while teleworking.